PRAKTEK TANGGUNG JAWAB SOSIAL PERUSAHAAN DI PROVINSI RIAU: TINJAUAN ATAS HARAPAN DAN KENYATAAN - Meirwin, Meirwin (JURNAL AL-IQTISHAD, 2013)
This paper tries to find out the expectation and realities of corporate social responsibility (CSR) activities in Riau Provinsi. 172 respondents were participated in this research. Based on the data, it concluded that more than fifty percent respondents feel the CSR activities in Riau Provinsi are below their expectation. This study also explored several positive and negative impact of companies operated in Riau Province. It is important to note that 70% responden didnât have any idea for what companies who come first into mind when thinking about socially responsible companies in Riau Province. To be socially responsible, companies should pay attention in several issues like employee, goods and service, community, and charity programs.